The influence of inter-turn short circuit fault considering loop current on the electromagnetic field of permanent magnet synchronous motor. Issue 4 (3rd July 2017) - Qiu, Hongbo; Yu, Wenfei; Yuan, Shuai; Tang, Bingxia; Yang, Cunxiang
Abstract : Purpose: The impact of the loop current (LC) on the motor magnetic field in the analysis of the inter-turn short circuit (ITSC) fault is always ignored. This paper made a comparative study on the electromagnetic field of permanent magnet synchronous motors (PMSM). The purpose of this study is to explore the necessary of the LC existing in the fault analysis and the electromagnetic characteristics of the PMSM with the ITSC fault when taking into account the LC. Design/methodology/approach: Based on the finite element method (FEM), the fault model was established, and the magnetic density of the fault condition was analyzed. The induced electromotive force (EMF) and the LC of the short circuit ring were studied. The three-phase induced EMF and the unbalance of the three-phase current under the fault condition were studied. Finally, a prototype test platform was built to obtain the data of the fault. Findings: The influence of the fault on the magnetic density was obtained. The current phase lag when the ITSC fault occurs causes the magnetic enhancement of the armature reaction. The mechanism that LC hinders the flux change was revealed. The influence of the fault on the three-phase-induced EMF symmetry, the three-phase current balance and the loss was obtained. Originality/value: The value of the LC in the short circuit ring and the influence of it on the motor electromagnetic field were obtained. On the basis of the electromagnetic field calculation model, the sensitivity of the LC to the magnetic density, induced EMF, current and loss were analyzed.